2022
DOI: 10.1038/s41598-022-11924-z
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity for information predicts wellbeing mediated by loneliness during COVID-19 pandemic

Abstract: The COVID-19 pandemic confronted humans with high uncertainty and lockdowns, which severely disrupted people’s daily social and health lifestyles, enhanced loneliness, and reduced well-being. Curiosity and information-seeking are central to behavior, fostering well-being and adaptation in changing environments. They may be particularly important to maintain well-being during the pandemic. Here, we investigated which motives drive information-seeking, and whether and how curiosity and information-seeking relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
6
1
Order By: Relevance
“…Based on previous studies on schizophrenia ( 40 ), we also examined whether food intake indexed by certain nutrient compositions (e.g., carbs, fat, fruit, and vegetables) is associated with CAPE. More in details, high total intake of fruit and vegetables has been associated with better mental health ( 22 , 41 , 42 ). In line with this evidence, several studies reported a negative association between dietary intake of fruits and vegetables and the presence of psychosis ( 40 , 41 , 43 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous studies on schizophrenia ( 40 ), we also examined whether food intake indexed by certain nutrient compositions (e.g., carbs, fat, fruit, and vegetables) is associated with CAPE. More in details, high total intake of fruit and vegetables has been associated with better mental health ( 22 , 41 , 42 ). In line with this evidence, several studies reported a negative association between dietary intake of fruits and vegetables and the presence of psychosis ( 40 , 41 , 43 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the dopaminergic precursor tyrosine and the serotoninergic precursor tryptophan, studies have reported their crucial role in motivation and mood, respectively. For example, it has been shown that acute tyrosine and tryptophan depletions can reduce motivation for reward and lower mood ( 22 , 37 , 51 , 52 ). Simultaneously, dopamine and serotonin play an important role in psychosis ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Neuroticism is negatively related to these measures ( Aschwanden et al, 2021 ; Kekäläinen et al, 2021 ; Kaspar and Nordmeyer, 2022 ; Moore et al, 2022 ; Otterbring and Festila, 2022 ). Additionally, previous studies have demonstrated the significant influence of the following personality traits, including aversion to infection ( Stangier et al, 2021 ), self-control ( Rodriguez et al, 2023 ), internal and external locus of control ( Krampe et al, 2021 ), cultural values ( Lu et al, 2021 ), curiosity ( Losecaat Vermeer et al, 2022 ), and optimism ( Sheetal et al, 2020 ) on health-protective behaviors.…”
Section: Introductionmentioning
confidence: 99%